Diagnostic test accuracy of dipstick urinalysis for diagnosing urinary tract infection in febrile infants attending the emergency department - Durnin, Sheena (My University, 2022)
Objective To report the diagnostic test accuracy of dipstick urinalysis for the detection of urinary tract infections (UTIs) in febrile infants aged 90 days or less attending the emergency department (ED). Design Retrospective cohort study. Patients Febrile infants aged 90 days or less attending between 31 August 2018 and 1 September 2019. Main outcome measures The sensitivity, specificity and predictive values of dipstick urinalysis in detecting UTIs defined as growth of ≥100 000 cfu/mL of a single organism and the presence of pyuria (>5 white blood cells per high-power field). Setting Eight paediatric EDs in the UK/Ireland. Results A total of 275 were included in the final analysis. There were 252 (92%) clean-catch urine samples and 23 (8%) were transurethral bladder catheter samples. The median age was 51 days (IQR 35–68.5, range 1–90), and there were 151/275 male participants (54.9%). In total, 38 (13.8%) participants had a confirmed UTI. The most sensitive individual dipstick test for UTI was the presence of leucocytes. Including ‘trace’ as positive resulted in a sensitivity of 0.87 (95% CI 0.69 to 0.94) and a specificity of 0.73 (95% CI 0.67 to 0.79). The most specific individual dipstick test for UTI was the presence of nitrites. Including trace as positive resulted in a specificity of 0.91 (95% CI 0.86 to 0.94) and a sensitivity of 0.42 (95% CI 0.26 to 0.59). Conclusion Point-of-care urinalysis is moderately sensitive and highly specific for diagnosing UTI in febrile infants. The optimum cut-point to for excluding UTI was leucocytes (1+), and the optimum cut-point for confirming UTI was nitrites (trace).
PUBLISHED
Keywords: Urinary tract infection; Urinalysis; Leucocytes; Nitrites; Immunology, Inflammation & Infection; URINARY TRACT INFECTION; URINE; URINE SAMPLES